Mural nodule of Anaplastic Carcinoma in an Ovarian Mucinous Cystadenoma- A rare case report - K., Subashree; M., Lavanya; C., Jayanthi; Maria (Tropical Journal of Pathology and Microbiology, 2020)
Mucinous tumors account approximately for 15% of all primary ovarian epithelial neoplasms. Ovarian mucinous tumors with mural nodules are rare surface epithelial-stromal tumorswhich can be of three types, “sarcoma-like”, sarcoma or anaplastic carcinoma. Mural nodules of anaplastic carcinoma were first described in 1982 by Prat et al following which approximately fifty cases have been reported to date and in those cases, only one has been associated with benign mucinous tumors. The current case report is from a 50-year-oldpostmenopausal woman who presented to the gynecology outpatient department with complaints of abdominal pain and distension for the past five months. On histopathological examination, a diagnosis of Mucinous cystadenoma with focal atypia and mural nodule of anaplastic carcinoma was made and confirmed with immunohistochemistry.